Delta Neutrophil Index as a Diagnostic Marker of Neonatal Sepsis - Melekoglu, Nuriye Asli; Yasar, Seyma; Keskin, Mehmet (Journal of Pediatric Infectious Diseases, 2021)
Objective Sepsis diagnosis is challenging due to nonspecific symptomatology in newborns. Timely diagnosis is essential for reducing sepsis-related morbidity and mortality. This study was performed to determine the diagnostic value of the delta neutrophil index (DNI) for detection of neonatal sepsis and to compare its efficacy with other conventional markers.Methods This study was conducted at a tertiary hospital in newborns with confirmed sepsis (n = 59), suspected sepsis (n = 46), and in age- and weight-matched controls (n = 49). DNI, white blood cell count, C-reactive protein (CRP) level, and platelet measurements were determined, and blood cultures were performed at the onset of symptoms.Results The mean DNI was significantly higher in confirmed and clinical sepsis groups compared with the control group. (6.9 ± 9.3, 1.9 ± 2.1, and 0.4 ± 0.5, respectively, p < 0.001). ROC curve analysis also showed that the combination of DNI and CRP had the highest sensitivity (86%), specificity (100%), and positive predictive value (100%) for predicting neonatal sepsis. DNI values were significantly higher in nonsurvivors (p < 0.05).Conclusion DNI could be used as a reliable diagnostic marker for neonatal sepsis, and high DNI could predict sepsis development and unfavorable outcomes. The diagnostic capability of DNI may be increased by assessing CRP measurements simultaneously.
Keywords: delta neutrophil index; sepsis; newborn